Corporate Governance and Board Gender Diversity as Moderators of Environmental Innovation on Financial Performance in Indonesia - Rina Yuniarti; Husaini Husaini; Soedjatmiko Soedjatmiko (JASF: Journal of Accounting and Strategic Finance, 2026)
Purpose: Focusing on environmental strategic practices, this study examines whether Environmental Performance and carbon emission disclosure generate financial value and whether such value is contingent upon gender diversity and corporate governance mechanisms. This study emphasizes the strategic role of internal governance mechanisms in optimizing financial returns from environmental initiatives, especially in Indonesia, where regulatory and environmental pressures are intensifying. Method: Using a quantitative approach, this study uses secondary data from annual and sustainability reports of firms listed on the Indonesia Stock Exchange for 2023–2024. Environmental innovation was measured using Environmental Disclosure Index based on environmental information disclosed. Carbon emission disclosure was assessed based on GRI 305 indicators, financial performance was proxied by Return on Assets (ROA), gender diversity was measured by the proportion of female directors/commissioners, and corporate governance was proxied by the proportion of independent commissioners. Using purposive sampling, the study obtained 354 firm-year observations from 177 firms. The hypotheses were tested using Partial Least Squares Structural Equation Modelling (PLS-SEM). Findings: Model estimation results show that both environmental innovation and carbon transparency are associated with improved profitability. Importantly, this relationship intensifies in the presence of heterogeneous board representation and effective governance controls, underscoring the conditional nature of sustainability-driven financial gains. Implications: The findings provide practical implications for corporate managers in strengthening sustainability-oriented governance strategies, for investors in evaluating firms’ long-term sustainability performance, and for regulators and policymakers in encouraging stronger environmental disclosure and board diversity practices in emerging markets such as Indonesia. Novelty/Value: Unlike prior studies in Indonesia that primarily examine the direct effect of environmental practices on financial performance, this study develops an integrated framework by investigating the simultaneous moderating roles of gender diversity and corporate governance in the relationship between environmental strategies and financial performance. The study extends the stakeholder and contingency perspectives in emerging markets.